Does securitization for government staff personal loan perform? - Bakri, Mohammed Hariri; Dabas, Nurayati; Ismail, Shafinar; Abdul Hamid, Baharom (Science Publishing Corporation, 2018)
Malaysian firms have been reported to involve in Asset-Backed Securities since 1986s where Cagamas is a pioneer. The objective of this study to determine the primary market spread and analyze on firm financial performance. The methodology for this paper using regression analysis for the study period 2007-2012. They are three determinants that contribute and statistically significant for this research paper. The measurement of financial performance does not have any impact during subprime mortgage crisis. The firm results shows increasing profitability, reducing debt, stronger company value and shareholders earning better dividend.